(untitled) (Quaderni di Gargnano, 2022)
This essay reviews and analyzes the argumentative structure of Convivio IV vi, in which Dante traces a brief but noteworthy history of moral philosophy in Antiquity. He offers particular attention to the debates on human happiness pursued by the Stoics, Epicureans, and Academics, arguing that these reached their climax with Aristotle and his Peripatetic school. This conclusion prompts an enthusiastic eulogy of the Philosopher as master and leader (maestro and duca) of human reason. The article investigates this eulogy’s doctrinal foundations and reviews its persistent vitality in Dante’s work (particularly in the Monarchia), as well as discussing the opposing judgment on Aristotle formulated by Petrarch in De ignorantia. Il saggio ripercorre e analizza la struttura argomentativa di Convivio IV vi, nel quale Dante traccia una breve ma interessante storia della scienza morale antica. In particolare l’autore considera le tesi di Stoici, Epicurei ed Accademici intorno alla felicità umana e rinviene nella posizione dei Peripatetici, e del loro caposcuola Aristotele, il culmine di questa ricerca. Ciò fornisce l’occasione a Dante per comporre un altissimo elogio del Filosofo, maestro e duca della ragione umana. L’articolo indaga i fondamenti dottrinari di questo elogio e la sua vitalità nell’opera dantesca (segnatamente nella Monarchia), mostrando al contempo come ad esso si opponga il giudizio su Aristotele formulato da Petrarca nel De ignorantia.